Frequency And Duration Of Rest And Intensity Of Lighting Effect On Computer Vision Syndrome In Medical Student Of Islamic University Of Malang - Ramadhani Prasetyo, Muhammad Gusti; Indria, Dewi Martha; Dewi, Ariani Ratri (Indonesian Health Journal, 2025)
In today's modern era, gadget use is integral to human activities, including higher education. Prolonged use of gadgets with inadequate breaks and unbalanced lighting intensity can lead to Computer Vision Syndrome (CVS), a range of eye, vision, and non-eye symptoms associated with gadget use. This research investigates the impact of rest frequency, duration of rest, and lighting intensity on CVS among medical students. This research was an analytical, quantitative, cross-sectional observational study, with second and third year medical students as respondents (total sampling). CVS was assessed using the Computer Vision Syndrome Questionnaire (CVS-Q), frequency and duration of rest were obtained through a questionnaire, and light intensity was measured using a lux-meter. Statistical analysis used the Chi-Square test for influence and binary logistic regression test for odds ratio. Among the 181 respondents, aged approximately 18-22 years, 48% (88 individuals) reported suffering from CVS (CVS-Q 9.65 ± 3.43). The study found that 56.35% of the respondents rested after more than 20 minutes, and 53% rested for less than 20 seconds each time. Additionally, unbalanced lighting intensity between the gadget screen and surrounding light was observed in 50.82% of the respondents (92 individuals). The Chi-square test revealed a pvalue of 0.000, indicating a significant effect of rest frequency, rest duration, and lighting intensity on the CVS-Q score. There is an influence of frequency and duration of rest and lighting intensity on increasing CVS scores.